Measuring strategic firm interaction in product-quality choices: The case of airline flight frequency - Jan K. Brueckner; Dan Luo (Center for Economic Studies and ifo Institute (CESifo), 2013)
This paper investigates strategic interaction among airlines in product-quality choices. Using an instrumental variables approach, the paper estimates flight-frequency reaction functions, which relate an airline's frequency on a route to its own characteristics and to the frequencies of competing airlines. A positive reaction function slope is found in some cases, indicating the presence of strategic interaction in the choice of frequencies. The paper also asks whether multimarket contact generates mutual forbearance in frequency competition, finding no evidence for such an effect.
Keywords: L10; L93; 330; airlines; reaction function; product quality; flight frequency; Luftverkehrsgesellschaft; Dienstleistungsqualität; Wettbewerb; Reaktionsfunktion; Theorie; Schätzung; USA